Komunikasi lintas budaya : petunjuk praktis untuk komunikasi bisnis internasional=Bridging the culture gap6ba practical guide to intenational business communication - Carte, Penny (Indek, 2006)
Judul asli Bridging the culture gab a practical guide to international business communication